The Social and Vocational Value and Outcomes of the New South Wales School Infrastructure Traineeship Program (ITP) for Trainees - Brown, Seth; Kershaw Phillips, Scott; Rushbrook, Peter; Cooper, Grant; Kelly, Peter (2023)
This Report presents the findings of research conducted to measure the social and vocational value and outcomes of the Infrastructure Traineeship Program (ITP) for trainees and to provide evidence that can be used: ● to advocate for the future directions for the program considered within a broader context of the contribution this program may make to delivering on New South Wales (NSW) Government’s 10 Point Commitment to the construction sector, providing better employment outcomes for young people, women, and young people from regional areas to work near home. ● to demonstrate the challenges and opportunities that the ITP affords in providing a pathway to young people, including First Nations young people, into a career in infrastructure referencing the NSW Treasury’s framework and outcomes to support First Nations economic wellbeing and prosperity.